Money and monetary policy transmission in the euro area: evidence from FAVAR- and VAR approaches - Barno Blaes (Deutsche Bundesbank, 2009)
This paper investigates the transmission of monetary policy in the euro area based on the factor augmented vector autoregressive approach of Bernanke, Boivin and Eliasz (2005) as well as on a standard VAR model. We focus on the reaction of monetary aggregates to a one-off monetary policy shock. We find that - as theory suggests - money growth is dampened by a restrictive monetary policy stance in the longer term. In the short-run, however, M3 growth may increase due to portfolio shifts caused by the rise in the short-term interest rate. This has consequences for the interpretation of money growth as an input for monetary policy decisions.
Keywords: C32; E40; E52; 330; Monetary policy transmission; FAVAR; VAR; money stock; euro area.; Geldpolitik; Transmissionsmechanismus; Geldmenge; Europäische Wirtschafts- und Währungsunion; VAR-Modell; Schätzung; EU-Staaten